2018
DOI: 10.1007/s00330-018-5517-9
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave elastography: a new potential method to diagnose ulnar neuropathy at the elbow

Abstract: ObjectivesThe primary aim of this study was to verify if shear-wave elastography (SWE) can be used to diagnose ulnar neuropathy at the elbow (UNE). The secondary objective was to compare the cross-sectional areas (CSA) of the ulnar nerve in the cubital tunnel and to determine a cut-off value for this parameter accurately identifying persons with UNE.MethodsThe study included 34 patients with UNE (mean age, 59.35 years) and 38 healthy controls (mean age, 57.42 years). Each participant was subjected to SWE of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 53 publications
7
58
3
Order By: Relevance
“…With elbow position held constant, we found a statistically significant difference in SW velocity between proximal and distal locations for the ulnar nerve but not for the median nerve. These results are in line with previous findings, some of which have shown localized differences in nerve SW velocity, while others have not . The reason for this disparity is likely due to nerve and location examined because nerve tension and structure are not uniform along the limb and differ with proximity to joints …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With elbow position held constant, we found a statistically significant difference in SW velocity between proximal and distal locations for the ulnar nerve but not for the median nerve. These results are in line with previous findings, some of which have shown localized differences in nerve SW velocity, while others have not . The reason for this disparity is likely due to nerve and location examined because nerve tension and structure are not uniform along the limb and differ with proximity to joints …”
Section: Discussionsupporting
confidence: 92%
“…We found no definitive relationship between nerve SW velocity and morphometry in unimpaired nerves such as has been found in patients with diabetic and entrapment neuropathies . Therefore, it is unlikely that differences observed in SW velocity were a result of variation in nerve morphometry.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…There is presently only sparse data regarding the use of ultrasound elastography as a diagnostic modality in UNE. Like CTS, the studies have shown increased nerve stiffness at the site of injury but a relationship between the severity of ulnar neuropathy and ultrasound elastography values was not established . Increased nerve stiffness has also been identified in patients with ulnar neuropathy in Guyon's canal at the wrist .…”
Section: Resultsmentioning
confidence: 99%
“…Like CTS, the studies have shown increased nerve stiffness at the site of injury but a relationship between the severity of ulnar neuropathy and ultrasound elastography values was not established. 46,47 Increased nerve stiffness has also been identified in patients with ulnar neuropathy in Guyon's canal at the wrist. 48 Based on currently published data, the role of elastography in the diagnosis of ulnar neuropathy remains unclear.…”
Section: Ulnar Neuropathymentioning
confidence: 99%